Kontekstualisasi Hukum Berperspektif Perempuan di Peradilan Agama - Hj Asni (Al-'Adl, 2016)
This study focused on the urgency of the Religious Courts role in providing protection for the rights of women. Female perspective important to presented in Religion Court decision because the ideas that the protection of women in the Marriage Law and the Compilation of Islamic Law and other legal products need a application in a court. In addition, laws related to women, sometimes has special characteristics so that the position of women in certain cases important to get the defense of the judge. The decisions of the Religious Court must be deep elaborated beside applying the legal norms contained in the law to protect the rights of women. Therefore, we need specific strategies such as emphasized the need for the law by the judge as well as the importance of women's awareness of their own on their rights.